Effectiveness of Education based on Health Belief Model (HBM) on Preventive Behaviors of Pesticide Exposure in Agricultural Worker - SS MazloomiMahmoodabad (Toloo-e-behdasht, 2016)
Introduction: There have been various problems toward farmers health associated with unscientific use of pesticide in developing countries including Iran. Considering of the nature of biocides, negative impacts of pesticides are inevitable, therefore the promotion of awareness of workers for prevention of diseases is important. The purpose of this study was to assess the effectiveness of HBM in promoting Preventive behaviors of pesticide exposure.